Global humanitarianism and media culture - Tavernor, Rachel; Lawrence, Michael, 1973- (Humanitarianism (Series), 2019)
This collection interrogates the representation of humanitarian crisis, catastrophe and care. Contributors explore the refraction of humanitarian intervention from the mid-twentieth century to the present across a diverse range of media forms, including screen media (film, television and online video), newspapers, memoirs, music festivals and social media platforms (notably Facebook, YouTube and Flickr). Examining the historical, cultural and political contexts that have shaped the mediation of humanitarian relationships since the middle of the twentieth century, the book reveals significant synergies between the humanitarian enterprise the endeavour to alleviate the suffering of particular groups - and its media representations, particularly in their modes of addressing and appealing to specific publics.